Dampak CSR terhadap Kesejahteraan Masyarakat Binaan Ternak PT. PLN Tanjung Jati B - Syarifuddin, Muhammad Chaniv (Universitas Negeri Semarang, 2020)
Corporate Social Responsibility (CSR), is the company's commitment to contribute to economic development that is supported by taking into account aspects of the partnership program and community development. PT. PLN TJB as one of the large and medium-sized industrial companies that runs CSR programs, namely the planning and implementation of the CSR program. This research was conducted to see the plan to implement the partnership and Community Development program implemented by PT. PLN TJB and see the effect of the Partnership and Community Development Program on the welfare of PT. PLN TJB. This research method is quantitative descriptive using primary data with the number of respondents as many as 50 people who are members of integrated livestock fostered groups. The analytical tool used is SPSS. The results showed the implementation of Corporate Social Responsibility implemented by PT. PLN TJB Goes Well. The CSR program received a positive response from the community. The community also welcomed the CSR program of PT. PLN TJB. The relationship between the implementation of CSR programs in partnership programs involves several parties, namely the CSR unit of PT. PLN TJB, Higher Education, Local Government, and Livestock-guided Community PT. PLN. Partnership implementation program through three stages of planning, implementation and evaluation. For the Community Development program the implementation of the CSR Program, PT. PLN TJB channeled aid to the community directly, but for infrastructure and the environment PT. PLN involves the village government in carrying out its CSR activities. The role of companies in village economic development is quite central. The company has a positive influence on society. CSR programs conducted by PT. PLN TJB has been quite successful with the welfare of the communities surrounding PT. PLN TJB. Like CSR in the economic field through flashlight programs and tourist villages that provide direct to the surrounding community. Free treatment program that gets enthusiastic from the community. Corporate Social Responsibility (CSR), adalah komitmen perusahaan dalam berkontribusi pada pengembangan ekonomi berkelanjutan dengan memerhatikan aspek program kemitraan dan bina lingkungan. PT. PLN TJB sebagai salah satu perusahaan industri besar dan beroperasi secara nasional memiliki permasalahan mendasar dalam penerapan CSR, yaitu perencanaan dan pelaksanaan program CSR tersebut. Penelitian ini dimaksudkan untuk melihat mekanisme pelaksanaan program kemitraan dan bina lingkungan yang dilaksanakan PT. PLN TJB serta melihat pengaruh Program kemitraan dan bina lingkungan terhadap kesejahteraan masyarakat binaan PT. PLN TJB. Metode dalam penelitian ini adalah kuantitatif diskriptif menggunakan data primer dengan jumlah responden sebanyak 50 orang yang tergabung dalam kelompok binaan ternak terpadu. Alat analisis yang digunakan adalah SPSS. Hasil penelitian menunjukkan Implementasi Corporate Social Responsibility yang dilaksanakan oleh PT. PLN TJB berjalan secara baik. Adanya program CSR mendapatkan respon positif dari masyarakat. Masyarakat juga antusias menyambut program CSR PT. PLN TJB. Mekanisme pelaksanaan program CSR pada program kemitraan melibatkan beberapa pihak yakni unit CSR PT. PLN TJB, Perguruan Tinggi, Pemerintah Daerah, serta Masyarakat kelompok binaan Ternak PT. PLN. Pelaksanaan program kemitraan melalui tiga tahapan yakni perencanaan, pelaksanaan dan evaluasi. Untuk program bina lingkungan mekanisme pelaksanaan program CSR, PT. PLN TJB menyalurkan alokasi bantuan ke masyarakat langsung, tetapi untuk infrastuktur dan lingkungan PT. PLN melibatkan pemerintah desa dalam pelaksanaan kegiatan CSR nya. Peran perusahaan dalam pembangunan ekonomi desa cukup sentral. Adanya perusahaan memberikan dampak positif terhadap masyarakat. Program CSR yang dilakukan PT. PLN TJB cukup berpengaruh terhdap kesejahteraan masyarakat sekitar PT. PLN TJB. Seperti CSR bidang ekonomi melalui program senter dan desa wisata yang memberikan dampak langsung ke pendapatan masyarakat sekitar. Serta program pengobatan gratis yang mendapatkan antusias dari masyarakat.